Potret Organisasi Jurnalis Pasca Orde Baru di Daerah Istimewa Yogyakarta - Masduki Masduki (Program Studi Ilmu Komunikasi, 2015)
Association of journalists is one of the press freedom pillars. Up to 15 years after the collapsed of New Order regime, there has been no comprehensive studies related to the performance of journalist's association in maintaining the press freedom, professionalism o/j their members and engagement in public issue advocacies. This paper describes the results of research on the portrait of journalist organizations in Yogyakarta, using qualitative method throughout the months ofMay-June 2015. This research found that two models: formal and nonp-formal associations existed, with the tendency of different solidity and independence. In addition to the lack of membership loyalty and funding, internal ego of the organization in carrying out the mission is a serious problem in the future.